IMPACT OF OLIGOETHER L - 501 - 2 - 100 ONTO THE OXIDANT-ANTIOXIDANT METABOLISM IN CONDITIONS OF ANTIRADICAL AND ANTIPEROXIDE COMPLEX - Bagmut, I.Yu.; Polishchuk, T.; Zhukov, V.; Klimenko, N.A. (World of Medicine and Biology, 2014)
In subacute experiment on 135 white rats the effects of oligoether L - 501 - 2 - 100 at a dose of 1/100 LD50 in administration of nutritional complex on the state of the oxidant-antioxidant metabolism has been investigated. Administration of of nutritional antiradical, antiperoxide complex inhibits free radical processes, lipid peroxidation, activates antioxidant system and increases the stability of biological membranes to the oligoether toxic effects.
Keywords: xenobiotics; correction; nutritional antioxidant complex; rats